Digital technology and practices for school improvement: innovative digital school model - Liisa Ilomäki; Minna Lakkala (The Asia-Pacific Society for Computers in Education (APSCE), 2018)
Abstract The aim of this study was to create a model which describes the main elements for improving schools with digital technology and helps to reveal differences between schools and identify their best practices and challenges. The innovative digital school model (IDI school) offers a framework for research but also a research-based model for schools to examine their own practices with digital technologies. The model combines previous research on school improvement, creation of innovations, and digital technology in education as a special case of innovations and learning as knowledge creation to define six main elements describing an innovative, digital school: visions of the school, leadership, practices of the teaching community, pedagogical practices, school-level knowledge practices and digital resources. The model was applied to investigate three basic education schools. The results indicate that the model worked: we found essential differences between the schools and their best practices and challenges for improvement. It worked particularly well for those elements, which are mainly the responsibility for leadership inside a school. The differences of various elements between schools were not based on socioeconomic background but on the school-level practices. As a conclusion, we suggest that to improve schools with digital technology, all elements of the model should be included in the evaluation and development process.